2013
DOI: 10.1057/jphp.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

A typology of beverage taxation: Multiple approaches for obesity prevention and obesity prevention-related revenue generation

Abstract: Obesity is a global problem. Sugar-sweetened beverages (SSB) are a leading contributor of added sugars in individual diets and thus to obesity. Governments have considered taxing SSBs to prevent obesity and generate revenue, but no ‘one-size-fits-all' taxation approach exists. We describes three key considerations for governments interested in exploring beverage taxation: (i) what type of tax to apply plus how and where the tax is collected and presented to consumers; (ii) what types of beverages to tax; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…Intervention evidence supporting food taxes is also limited (27). Simulation studies on the price elasticity of soda have demonstrated minimal impact on weight-related outcomes (80).…”
Section: Government Policiesmentioning
confidence: 99%
“…Intervention evidence supporting food taxes is also limited (27). Simulation studies on the price elasticity of soda have demonstrated minimal impact on weight-related outcomes (80).…”
Section: Government Policiesmentioning
confidence: 99%
“…The revenues of the tax could be further used for further public health actions against overweight and obesity, like subsidizing healthy drinks or foods [4]. SSB taxes are in place in several US states, Mexico and a number of European and Pacific countries [7, 11], and have been found effective for reducing SSB consumption in natural experiments [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, combining measurements of these policies may be more highly associated with soda consumption and weight status than when policy effects are explored individually, or they may serve to clarify discrepancies in the literature regarding how policy affects these outcomes. Alternatively, the ability to detect association of these combined policy approaches with soda consumption and weight status may still be limited, since state soda taxes are relatively small in comparison to other taxes (3?54 % soda sales tax v. 5?2 % tobacco sales tax on average) (9,10,22) , such as those applying to cigarettes that have been shown to influence adolescent behaviour (23) . However, since it is predicted that soda sales tax rates .6 % are necessary to reduced soda consumption and SSB price elasticity is estimated to be 21?21 (5) , identifying complementary policies in a state that reduce SSB consumption significantly may present an opportunity to support other states in enacting similar policies.…”
Section: Discussionmentioning
confidence: 99%